Simulated Biosorption of Cd(II) and Cu(II) in Single and Binary Metal Systems by Water Hyacinth (Eichhornia crassipes) using Aspen Adsorption - Adonis P. Adornado; Allan N. Soriano; Omar Nassif Orfiana; Mark Brandon J. Pangon; Aileen D. Nieva (Department of Chemical Engineering, Universitas Gadjah Mada, 2017)
Biosorption is becoming an attractive alternative for the removal of heavy metal from contaminated wastewaters since it offers low capital and operating costs. It has a great potential on heavy metal decontamination and the possibility of metal recovery. The study evaluated the performance of water hyacinth (Eichhornia crassipes) in a fixed bed column on sequestering heavy metals present in wastewaters. Column breakthrough curves at varying parameters were evaluated. The study used Aspen Adsorption® to simulate the biosorption process. Analysis of breakthrough curves for the single metal system shows that increasing both influent flow rate and initial metal concentration reduces the metal uptake of the column, while increasing bed height enhances the metal uptake of the column. Presence of both Cd(II) and Cu(II) in the system promotes competitive sorption processes. Analysis of the breakthrough curves for the binary metal system showed that copper ions adsorbed to the adsorbent are replaced by cadmium ions when the maximum capacity of the column is reached. This leads to the outlet concentration of Cu(II) exceeding its initial concentration. This phenomenon shows that Cd(II) has more affinity with E. crassipes than Cu(II).